2007
DOI: 10.1525/mp.2007.25.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Viewers' Interpretations of Film Characters' Emotions: Effects of Presenting Film Music Before or After a Character is Shown

Abstract: STUDIES ADDRESSING EFFECTS OF MUSIC ON VIEWERS' perceptions of film have usually presented music simultaneously with a scene of interest. In the present study, 177 undergraduates viewed film excerpts with music presented before or after a scene featuring a single character. Whereas the film characters had emotionally neutral or subdued facial expressions, the music conveyed happiness, sadness, fear, or anger. Overall, participants tended to interpret characters' emotions in ways that were consistent with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…While other studies have found relationships between music and its influence on the interpretation of the relationship between two characters in a scene (Boltz, 2001), the guidance towards a particular character identity (Shevy, 2007), the sensation of closure to a given scene (Thompson, Russo, & Sinclair, 1994), or it's effect on the perception of emotion from what a neutrally expressed character is feeling (Tan, Spackman, & Bezdek, 2007), music can also bring forth attention to a specific visual aspect within the film (Bolivar, Cohen, and Fentress, 1994;Marshall and Cohen, 1988). For instance, an example of this change from structural congruency to semantic congruencies could include the use of a lullaby that directs a spectator's attention towards a baby's crib within a scene.…”
Section: Psychological Responses To Film and Musicmentioning
confidence: 94%
“…While other studies have found relationships between music and its influence on the interpretation of the relationship between two characters in a scene (Boltz, 2001), the guidance towards a particular character identity (Shevy, 2007), the sensation of closure to a given scene (Thompson, Russo, & Sinclair, 1994), or it's effect on the perception of emotion from what a neutrally expressed character is feeling (Tan, Spackman, & Bezdek, 2007), music can also bring forth attention to a specific visual aspect within the film (Bolivar, Cohen, and Fentress, 1994;Marshall and Cohen, 1988). For instance, an example of this change from structural congruency to semantic congruencies could include the use of a lullaby that directs a spectator's attention towards a baby's crib within a scene.…”
Section: Psychological Responses To Film and Musicmentioning
confidence: 94%
“…1Four representations of narrative theories of literature and movies. Aristotle’s is based on his Poetics (Upton, 1746); Freytag’s comes from Technique of the Drama (MacEwan, 1900, p. 115); Field’s from Screenplay: The Foundations of Screen Writing (Field, 2005); and Thompson’s is based on Storytelling in the New Hollywood (Thompson, 1999). Elaborations in red come from others, cited in the text …”
Section: Narrative Theory In Theater and Moviesmentioning
confidence: 99%
“…It will be useful, however, to discuss one, but to do so I must first define two terms suggested in their use by Thompson (1999, p. 23). First, turning points are narrative moments from which the plot goes in a different direction.…”
Section: Narrative Theory In Theater and Moviesmentioning
confidence: 99%
See 1 more Smart Citation
“…A final approach we will mention that again focusses on narrative in general comes from previous film music studies, in which researchers tested the effects of different musical conditions on viewers' interpretation of ambiguous film scenes [22,40,14,3]. For example, Bravo [3] created two chord progressions that were meant to be similar except in their amount of harmonic dissonance; he then played them in separate conditions alongside the same film clip (an ambiguous scene with a single character), and asked participants to respond to a series of questions about the film.…”
Section: Conveyance Of Narrativementioning
confidence: 99%